Reconstructing identity and purpose in the athlete-to-coach transition: a cross-case analysis of two contrasting division i graduate assistant coaches in the United States - Yukhymenko-Lescroart, M. A. (International Sport Coaching Journal, 2025)
The pathway to becoming a coach often begins with playing the sport as an athlete; yet, the athlete-to-coach transition often presents challenges concerning self-comprehension, encompassing both one`s sense of self and overall purpose in life. Through a qualitative case study approach, this study sought to examine the athlete-to-coach transition experiences of two contrasting Division I graduate assistant coaches in the United States: one in men`s football and one in women`s softball. Employing in-depth interviews and thematic analysis, a "case-based" approach followed by a cross-case synthesis showed the main themes of (a) athlete-to-coach transition experiences (process, challenges, and the role of athletic experiences); (b) identity transformation (as an athlete, postathletic redefinition of self, emerging identity as a coach, and major shifts in self-views during each major phase); and (c) shifts in life purpose (process, challenges, and orientation: self vs. others focused). Recommendations for supporting graduate assistant coaches are discussed.